Mice Deficient for Testis-Brain RNA-Binding Protein Exhibit a Coordinate Loss of TRAX, Reduced Fertility, Altered Gene Expression in the Brain, and Behavioral Changes - Chennathukuzhi, Vargheese (American Society for Microbiology, 2003)
Testis-brain RNA-binding protein (TB-RBP), the mouse orthologue of the human protein Translin, is a widely expressed and highly conserved protein with proposed functions in chromosomal translocations, mitotic cell division, and mRNA transport and storage. To better define the biological roles of TB-RBP, we generated mice lacking TB-RBP. Matings between heterozygotes gave rise to viable, apparently normal homozygous mutant mice at a normal Mendelian ratio. The TB-RBP-related and -interacting protein Translin-associated factor X was reduced to 50% normal levels in heterozygotes and was absent in TB-RBP-null animals. The null mice were 10 to 30% smaller than their wild-type or heterozygote littermates at birth and remained so to about 6 to 9 months of age, showed normal B- and T-cell development, and accumulated visceral fat. TB-RBP-null male mice were fertile and sired offspring but had abnormal seminiferous tubules and reduced sperm counts. Null female mice were subfertile and had reduced litter sizes. Microarray analysis of total brain RNA from null and wild-type mice revealed an altered gene expression profile with the up-regulation of 14 genes and the down-regulation of 217 genes out of 12,473 probe sets. Numerous neurotransmitter receptors and ion channels, including γ-aminobutyric acid A receptor α1 and glutamate receptor α3, were strongly down-regulated. Behavioral abnormalities were also seen. Compared to littermates, the TB-RBP-null mice appeared docile and exhibited reduced Rota-Rod performance.